The political activity analysis in social media during the first electoral round of the 2021 general elections in Peru - Montúfar-Calle, Álvaro (2022)
The 2021 general elections in Peru took place in an unusual context generated by many factors. In addition to taking place within the bicentennial year of the country's independence and having eighteen presidential candidates, the electoral process was marked by a deep political crisis and the COVID-19 pandemic. In this context, the present research aims to understand how the political communication of the candidates and their political parties was managed on social media during the first round of these presidential elections. To find this, a metric analysis is applied oriented to the presence and activity of candidates and political parties in social media. The findings reveal a high level of presence of candidates and political parties, a clear phenomenon of personalization in political communication and the concentration of posts, especially in Facebook and Twitter.